2007
DOI: 10.1002/bsl.759
|View full text |Cite
|
Sign up to set email alerts
|

Plea bargaining recommendations by criminal defense attorneys: evidence strength, potential sentence, and defendant preference

Abstract: Although most criminal cases are disposed of through the process of plea bargaining, little research has focused on this process, and that research has focused on two variables: probability of conviction and potential sentence. This study examined the plea bargaining process from the perspective of the criminal defense attorney and expands prior research by including a third variable: defendant preference regarding plea. Attorney participants (N = 186) responded to a survey containing a vignette presented in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
52
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 15 publications
6
52
0
1
Order By: Relevance
“…There have been two partial replications of the Rossman, McDonald, and Cramer () hypothetical plea simulation design (Kramer, Wolbransky, and Heilbrun, ; McAllister and Bregman, ) . Both studies found that defense attorneys were more likely to advise a plea when cases were stronger, and McAllister and Bregman () found that prosecutors were less willing to plea bargain when cases were strong.…”
Section: Literature Review Of Empirical Models Of Plea Bargainingmentioning
confidence: 99%
“…There have been two partial replications of the Rossman, McDonald, and Cramer () hypothetical plea simulation design (Kramer, Wolbransky, and Heilbrun, ; McAllister and Bregman, ) . Both studies found that defense attorneys were more likely to advise a plea when cases were stronger, and McAllister and Bregman () found that prosecutors were less willing to plea bargain when cases were strong.…”
Section: Literature Review Of Empirical Models Of Plea Bargainingmentioning
confidence: 99%
“…La plupart des recherches s'accordent pour dire que la force de la preuve est un élément déterminant dans la décision d'entamer des négociations ou de plaider coupable, car elle permet d'estimer les probabilités de condamnation en cas de procès (Kramer, Wolbransky et Heilbrun, 2007). Frenzel et Ball (2007) montrent ensuite que la classe et le type d'infraction sont généralement les meilleurs prédicteurs de la décision de plaider coupable : il y a plus de plaidoyers de culpabilité pour les infractions les plus graves, ainsi que pour celles contre la drogue et la propriété.…”
Section: Les Caractéristiques Des Causes Ou Des Accusésunclassified
“…No study has been conducted to measure how attorneys view PSPs. A review of the available literature reflected that attorney perceptions have been previously measured on issues related to the pretrial or trial process, such as suspect lineups, witness credibility, client competence, and plea bargaining (Bonnie, Poythress, Hoge, Monahan, & Eisenberg, 1996;Foot, Stolberg, & Shepherd, 2000;Hoge, Bonnie, Poythress, & Monahan, 1992;Kramer, Wolbransky, & Heilbrun, 2007;Stinson, Devenport, Cutler, & Kravitz, 1996).…”
Section: Privatization In Community Correctionsmentioning
confidence: 99%